Weight-bearing MRI of the Lumbar Spine: Technical Aspects - Nordberg, Cecilie Lerche; Hansen, Bjarke Brandt; Nybing, Janus Damm; Hansen, Philip; Bliddal, Henning; Griffith, James F.; Fournier, Gilles; Guglielmi, Giuseppe; Boesen, Mikael (Seminars in Musculoskeletal Radiology, 2019)
Magnetic resonance imaging (MRI) has an established role in the assessment of degenerative musculoskeletal conditions. However, conventional supine MRI findings often correlate poorly with clinical findings. Some patients experience accentuated back pain in the weight-bearing position. Therefore, supine MRI may underestimate the severity of degenerative spine findings. To try and improve the clinical validity of spine imaging, axial loading devices have been used with conventional supine MR imaging to simulate loading of the upright spine. More recently, upright weight-bearing MRI systems (0.25–0.6 T) were introduced, allowing images to be obtained in the standing or seated weight-bearing position and even during upright flexion or extension, rotation, or bending. Some scanners even enable capturing of real-time spinal movement. This review addresses the technical aspects and potential challenges of weight-bearing MRI, both in clinical practice and research.
Keywords: magnetic resonance imaging; weight-bearing; spine; upright; lumbar